Effects of Si/Al molar ratio on strength endurance and volume stability of metakaolin geopolymers subject to elevated temperature - Lahoti, Mukund (2020)
Good structural performance in a fire scenario necessitates that the structural material possesses chemical stability, deformation resistance and strength endurance. Excellent chemical stability for geopolymers has been reported in literature at a microscale. However, their performance at macroscale has not yet been systematically explored and the underlying mechanisms remain unexplained. In current study, effect of variation in Si/Al molar ratio on the meso- and macro-scale thermal stability of metakaolin geopolymers has been comprehensively investigated to discover the underlying mechanisms governing the performance. Results show that all the geopolymer samples experienced reduction in compressive strengths after exposure to high temperature up to 900 °C. Although, the geopolymer mixes exhibited good chemical stability at microscale, they possessed poor volume stability at mesoscale with very high thermal shrinkage. It was observed that thermal shrinkage induced crack formation dominates the residual strength for geopolymer mixes with Si/Al molar ratio ≤ 1.50, while densification of matrix is the governing factor of the residual strength for geopolymer mixes with Si/Al molar ratio > 1.50. Re-crystallization of nepheline at high temperature adversely affect the strength by inducing expansion and cracking of the geopolymer matrix. Geopolymer sample with Si/Al ratio 1.75 retained highest strength (6 MPa) because viscous sintering of geopolymer mixes with high Si/Al ratio at temperature beyond 600 °C enables localized healing of micro-cracks and densification of matrix which favored compressive strength gain after exposure to 900 °C. At an even higher Si/Al of 2.0, foaming of unreacted silica upon heating can lead to expansion and cracking of the sample which reduce the strength. It was observed that due to high degree of cracking damage and low residual strength retention, it is essential to improve the macro-scale stability of metakaolin geopolymers for structural fire resistance applications.